Optical Studies on VO2 Thin Films. Issue 1803 (14th May 2015) - Wang, Lei; Beebe, Melissa; Madaras, Scott E.; Klopf, John M.; Radue, Elizabeth; Li, Zhaozhu; Wincheski, Russell A.; Lu, Jiwei; Wolf, Stuart A.; Novikova, Irina; Lukaszew, Rosa A.
ABSTRACT: We have been interested in the plasmonic properties of alternative conducting materials to metals, such as conducting oxides, and we have recently expanded our studies to include highly correlated oxides, such as vanadium dioxide (VO2 ) thin films. VO2 exhibits a metal-insulator transition (MIT) just above ambient temperature at ∼ 340K. Interestingly, this transition can be induced thermally, optically or applying electric fields. Across the MIT, the optical properties are completely modified over a broad frequency range. We will present our recent optical investigations on the photon induced transition studies on such films, as well as the surface plasmon resonance (SPR) modulation in nanopatterned Au gratings by the thermally induced MIT in VO2 thin films, addressing possibilities of ultrafast SPR modulation with VO2 .